Пошаговое объяснение:
1 слагаемое = х + 1/6
2 слагаемое = 2 * (х + 1/6) = 2х + 2/6 = 2х + 1/3
3 слагаемое = х
Сумма = 7
х + 1/6 + 2х + 1/3 + х = 7
4х + 1/6 + 2/6 = 7
4х + 3/6 = 7
4х = 7 - 3/6
4х = 6. 3/6
4х = 39/6
х = 39/6 : 4
х = 39/6 * 1/4
х = 39/24
х = 13/8
х = 1. 5/8
1 слагаемое = (х+ 1/6) =
1. 5/8 + 1/6 = 1. 15/24 + 4/24 = 1. 19/24
2 слагаемое = (2х + 1/3) = 2 * 13/8 + 1/3 = 26/8 + 1/3 = 3. 2/8 + 1/3 = 3. 6/24 + 8/24 = 3. 14/24 = 3. 7/12
3 слагаемое = (х) = 1. 5/8
1. 19/24 + 3. 7/12 + 1. 5/8 = 1. 19/24 + 3. 14/24 + 1. 15/24 = 5. 48/24 = 7
Ах3= 57
А=57:3
А=19
ответ: 19